The a to Z of Australian Radio and Television - Moran, Albert; Keating, Chris (Rowman & Littlefield Publishers, 2009)
Australians have become increasingly visible outside of the country as speakers and actors in radio and television, their media moguls have frequently bought up foreign companies, and people around the world have been able to enjoy such Australian productions as The Flying Doctors, Neighbours, and Kath and Kim. The origins, early development, and later adaptations of radio and television show how Australia has gone from being a minor and rather parochial player to being a significant part of the international scene. The A to Z of Australian Radio and Television provides essential facts and information concerning the Australian radio and television industry. This is accomplished through the use of a chronology, an introductory essay, a bibliography, and hundreds of cross-referenced dictionary entries on directors, producers, writers, actors, television and radio series, and television and radio stations.